Penerapan Media Papan Waktu pada Materi Pengukuran untuk Meningkatkan Keterampilan Numerasi Siswa Kelas II MI - Midya Yuli Amreta; Siti Khoirun Nisa'; Ilma Ariestiana; Luluk Nurul Aini; Siti Kurniawati; Aulatul Mufidati; Ahmad Farid Zaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on observations at MI Darul Ulum Pasinan it was found that the numeracy skills of second-grade students, particularly in the area of time measurement, are relatively low. This is due to the limited use of interactive and concrete learning media, which causes students to struggle in understanding the concept of time as a whole. This research focuses on strengthening students' numeracy abilities by integrating the Time Board as a learning tool for time measurement topics. Data collection techniques involve observations, interviews, and the analysis of relevant documentation.The results indicate that the implementation of the Time Board makes students more actively participate and understand the concept of time better. This study is intended to support the advancement of teaching approaches that are both relevant and contextually appropriate.